The volume‐outcomes relationship in donation after circulatory death liver transplantation. Issue 6 (25th April 2022) - Delman, Aaron M.; Turner, Kevin M.; Ammann, Allison M.; Schepers, Emily; Vaysburg, Dennis M.; Cortez, Alex R.; Van Haren, Robert M.; Wilson, Greg C.; Shah, Shimul A.; Quillin, Ralph C.
Abstract: Background: Donation after circulatory death (DCD) liver transplantation (LT) has become an effective mechanism for expanding the donor pool and decreasing waitlist mortality. However, it is unclear if low‐volume DCD centers can achieve comparable outcomes to high‐volume centers. Methods: From 2011 to 2019 utilizing the United Network for Organ Sharing (UNOS) database, liver transplant centers were categorized into tertiles based on their annual volume of DCD LTs. Donor selection, recipient selection, and survival outcomes were compared between very‐low volume (VLV, n = 1–2 DCD LTs per year), low‐volume (LV, n = 3–5), and high‐volume (HV, n > 5) centers. Results: One hundred and ten centers performed 3273 DCD LTs. VLV‐centers performed 339 (10.4%), LV‐centers performed 627 (19.2%), and HV‐centers performed 2307 (70.4%) LTs. 30‐day, 90‐day, and 1‐year patient and graft survival were significantly increased at HV‐centers (all P < .05). Recipients at HV‐centers had shorter waitlist durations ( P < .01) and shorter hospital lengths of stay ( P < .01). On multivariable regression, undergoing DCD LT at a VLV‐center or LV‐center was associated with increased 1‐year patient mortality (VLV‐OR:1.73, 1.12–2.69) (LV‐OR: 1.42, 1.01–2.00) and 1‐year graft failure (VLV‐OR: 1.79, 1.24–2.58) (LV‐OR: 1.28, .95–1.72). Discussion: Increased annual DCD liver transplant volume is associated with improved patient and graft survival.